Estimation of Body Composition and Health Status in Women, PE Students, on-site of Outdoor Activities on Gazivode Lake – A Case Study Report - Popović, Jasna; Popović, Miloš; Ranković, Goran; Purenović-Ivanović, Tijana; Popović, Ružena (Innovare Journal of Education, 2023)
This paper is based on the results of the cross-sectional experiment that was implemented in the school year 2021/2022 among women students in the first year of bachelor studies at the Faculty of Sport and Physical Education (FSPE) in Leposavić, University of Priština (temporarily allocated in Kosovska Mitrovica). The study design model was implemented during the obligatory course Outdoor activities (2nd semester, weekly classes 1 + 4, and 15 + 60 classes per semester) for the first time. Body composition assessment was realized along with the pedagogical practice of summer outdoor activities camp on Gazivode Lake in Kosovo (as a practical exam study curriculum requirement). The sample includes seven women FSPE students. Based on the body composition and health status assessment, students’ results are presented in figures (for the evaluation of measured variables) and diagrams for estimating the individual student’s results. Comparative analysis of results within the group was used, considering the differences among examined students regarding calculated mean values, recorded min and max results, and confidence interval. The student profile model scores were selected according to the best results achieved in general placement in most variables and evaluated regarding the case study report. The results were evaluated based on the digital system for the assessment of body composition (Omron BF511) and the interpretation of results for the following variables: Body Fat (BF%), Visceral Fat (VF), Skeletal Muscles Percentage (SM%), Body Mass Index (BMI), and Resting Metabolic Rate (RMR). Health status assessments were performed by an electronic digital blood pressure monitor (Prizma YE660E) for the measurement of Systolic (SYS), Diastolic Blood Pressure (DIA), and Resting Heart Rate (RHR). The results show the expected intra-group differences in body composition parameters, which are not inherited conditionally, for all selected body parameters (except for BMI). However, most of the values are in the recommended range, especially those with small percentages of high BF% and BMI, as well as SM% values, indicating the heterogeneity of the participants, their sports orientation, health status, and level of physical activity.